2017
DOI: 10.1021/acs.jmedchem.7b00396
|View full text |Cite
|
Sign up to set email alerts
|

A Kinome-Wide Selective Radiolabeled TrkB/C Inhibitor for in Vitro and in Vivo Neuroimaging: Synthesis, Preclinical Evaluation, and First-in-Human

Abstract: The proto-oncogenes NTRK1/2/3 encode the tropomyosin receptor kinases TrkA/B/C which play pivotal roles in neurobiology and cancer. We describe herein the discovery of [C]-(R)-3 ([C]-(R)-IPMICF16), a first-in-class positron emission tomography (PET) TrkB/C-targeting radiolabeled kinase inhibitor lead. Relying on extensive human kinome vetting, we show that (R)-3 is the most potent and most selective TrkB/C inhibitor characterized to date. It is demonstrated that [C]-(R)-3 readily crosses the blood-brain barrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 63 publications
2
32
0
Order By: Relevance
“…This paper reports our efforts to address these two issues and thereby enable the routine automated production of clinical radiotracer doses by using our previously published Cu‐mediated radiofluorination of arylborons. Proof‐of‐concept is demonstrated through the synthesis of [ 18 F]‐( ± )‐IPMICF17 ( 2‐F ), a radiolabeled inhibitor of tropomyosin receptor kinase B/C (TrkB/C) that is currently being developed for PET imaging of TrkB/C …”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…This paper reports our efforts to address these two issues and thereby enable the routine automated production of clinical radiotracer doses by using our previously published Cu‐mediated radiofluorination of arylborons. Proof‐of‐concept is demonstrated through the synthesis of [ 18 F]‐( ± )‐IPMICF17 ( 2‐F ), a radiolabeled inhibitor of tropomyosin receptor kinase B/C (TrkB/C) that is currently being developed for PET imaging of TrkB/C …”
Section: Introductionmentioning
confidence: 77%
“…To challenge the chemistry further, the optimized [ 18 F]KF dissolution/order of addition with KOTf/K 2 CO 3 eluent was applied to the synthesis of [ 18 F]‐( ± )‐IPMICF17 ( 2‐F ), a PET radiotracer for TrkB/C that is currently being developed by the Schirrmacher and Scott groups (Scheme ) . We expected this molecule to be amenable to such labeling because it has been previously demonstrated that the 6‐(pyrrolidin‐1‐yl)imidazo[1,2‐b]pyridazine core does not inhibit Cu‐mediated fluorination reactions .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further investigate the binding selectivity, we performed heterologous blocking studies on rat and human brain tissues against a panel of kinase inhibitors, including the protodeboronation side product BOMPyD, type‐I pan‐Trk inhibitor ( R )‐IPMICF22 (TrkB/C IC 50 = 0.57/0.37 nM, respectively), type‐II pan‐Trk inhibitor PF‐06273340 (TrkA/B/C IC 50 = 6/4/3 nM, respectively), and CSF‐1R inhibitor BLZ945 (IC 50 = 1.2 nM) . Across all rat brain cortical regions (posterior, medial, and anterior cortices; Figure A) blocking with BOMPyD, a demethoxy analogue of dual Trk/CSF‐1R inhibitor GW2580 was the highest (Δ = 42.1 ± 6.8%; t (28) = 10.574, P < 0.001; n = 15).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, several positron emission tomography (PET) tracers based on type‐I TrkB/C inhibitors have been developed and evaluated in preclinical and clinical settings . In particular, [ 11 C]IPMICF16 and [ 18 F]TRACK (Figure A) were the first type‐I TKI‐based PET tracers used for endogenous kinase neuroimaging in nonhuman primates and humans . Two putative selective tracers for in vivo imaging of CSF‐1R have been reported to date as attractive candidates for the PET imaging of microglial activation beyond translocator protein (TSPO) (Figure B).…”
Section: Introductionmentioning
confidence: 99%